Navigating the Power Outages: Impact and Coping Strategies of Students in a South African University during Loadshedding (Journal of Student Affairs in Africa, 2024)
Loadshedding, the scheduled power outage implemented in South Africa, has significantly affected various sectors, including higher education institutions. This paper explores the impact of loadshedding on students in a South African university, focusing on the difficulties they face, and the coping strategies employed. The study adopts a mixed methods approach, combining quantitative data from a structured survey and qualitative insights from discussion interviews. The findings highlight the disruptions caused by loadshedding, including missed lectures, limited access to resources, and challenges in submitting assignments. Power outages also negatively affect students' mental health, leading to increased stress, anxiety, and feelings of isolation. The study emphasizes the need for support measures to address the mental health needs of students during loadshedding. Various coping strategies are identified, such as time management, alternative power sources, offline study materials, group study sessions, and self-care practices. Understanding and analysing these coping strategies are essential in mitigating the impact of loadshedding on students' academic progress and well-being. The study contributes to the understanding of loadshedding's multifaceted impact on students, providing insights for developing support measures and creating a conducive learning environment. These findings inform discussions among institutions, policymakers, and stakeholders to support students and address the challenges posed by loadshedding.
Keywords: Loadshedding; Academic Performance; Students; Mental Health; Coping Strategies